Primary high-grade myoepithelial carcinoma of the lung: A study of three cases illustrating frequent SMARCB1-deficiency and review of the literature - Agaimy, Abbas; Naroditsky, Inna; Ben-Izhak, Ofer (Annals of Diagnostic Pathology, 2021)
Primary myoepithelial carcinoma of the lung is exceptionally rare and, hence, remained poorly characterized. We present 3 tumors affecting 2 males and 1 female aged 60 to 84 years. Tumor size ranged from 4 to 10 cm. All presented as well circumscribed non-encapsulated peripheral solitary masses. One patient died postoperatively. The other two were lost to follow-up. Histologically, all tumors were high-grade with predominance of myxoid/chordoid (2) and rhabdoid (1) pattern. Immunohistochemistry (IHC) showed reactivity with vimentin, pankeratin, EMA and smooth muscle actin. Two tumors were SMARCB1-deficient (one with additional loss of SMARCA2 and PBRM1). RNA sequencing revealed no gene fusions. Review of reported cases (total: 16) showed that pulmonary myoepithelial carcinoma affects both sexes equally at a median age of 60 years (24–84), presents predominantly as peripheral masses (69%) in the lower lobes (66%) of smokers (70%) with a median size of 6 cm (1.5–13), and originates as high-grade de novo carcinoma. Forty percent of patients died of disease at a median of 12.5 months (0 to 62). Only 40% of patients were disease free at last follow-up (median, 9.5 months). Prominent lobulation and myxoid stroma were frequent histological features. Most tumors displayed variable combinations of epithelioid, spindle, plasmacytoid, clear, ovoid or round cells. Three of 6 tumors subjected to different RNA panels showed EWSR1 rearrangements (fused to PBX1, ZNF444 or to unknown partner). Two of 3 tumors lacking gene fusions were SMARCB1-deficient (both showed secondary EWSR1 FISH abnormalities due to 22q deletion). Primary pulmonary myoepithelial carcinoma is a rare aggressive malignancy that recapitulates its soft tissue and salivary counterpart. Exclusion of metastasis from other primaries is mandatory and can only be achieved by detailed clinical history and imaging.
CRIS-Team Scopus Importer:2021-06-18
Keywords: EWSR1; Lung; Myoepithelial carcinoma; Primary; SMARCB1; SWI/SNF